Youth Volunteering in Sport: A Case Study of The Benefits of "The European Voluntary Service" for a Sport Organization - Esra Erturan-Ogut E. (Sciendo, 2014)
The European Voluntary Service of the European Union is thought to play a key role in promoting and encouraging volunteering among young people. Integrating the social work of EVS volunteers into activities through sport organizations is believed to help develop the perception of volunteering as an element of social commitment. The aim of this study is to therefore examine a case of youth volunteering practice in an EVS project in Turkey within the context of the benefits of volunteering. Data was collected using various tools. These included semi-structured interviews, participant observation (non-structured), and document analyses. Content analyses were applied to the interview data. The study established that the EVS is a beneficial channel for youth volunteering and provides benefits for each of the parties: the volunteers, the organization, and the sport participants.